Degradation kinetics and prediction of primary intermediates of cephalexin in aqueous media - Aydogdu, Seyda; Hatipoglu, Arzu (SPRINGER/PLENUM PUBLISHERS, 2024)
The presence of pharmaceuticals such as the antibiotic cephalexin in aqueous environments increases public health concerns due to their adverse biological effects and antibiotic resistance. It may be promising to remove these compounds from the aquatic environment through degradation reactions that convert them into non-toxic products. For this purpose, Density Functional Theory (DFT) molecular orbital calculations were performed to investigate the kinetics and mechanism of the degradation reaction of cephalexin with the hydroxyl (OH) radical. Reaction rate constants and branching ratios for 11 different reaction paths were calculated in the temperature range of 200 to 400 K. The total rate constant was calculated as 7.05 x 109 M-1 s-1 and is in good agreement with the experimental value. According to the kinetic and thermodynamic results, it can be concluded that the hydroxyl radical preferentially attacks the beta-lactam ring. The effect of water on the reaction mechanism was investigated in both implicit and explicit solvation models. Explicitly added water molecules affect the degradation reaction kinetic so that the results become compatible with the experimental ones. Ecotoxicity and bioaccumulation calculations on cephalexin and its degradation products show that some of its degradation products are harmful.
Keywords: Cephalexin; Density Functional Theory; Aqueous medium; Kinetics; Toxicity; ENHANCED PHOTOCATALYTIC ACTIVITY; BETA-LACTAM ANTIBIOTICS; PHOTO-FENTON; CEPHALOSPORIN ANTIBIOTICS; TIO2 PHOTOCATALYSIS; WASTE-WATER; OXIDATION; TRANSFORMATION; REMOVAL; MECHANISM; Chemistry; Crystallography